2016
DOI: 10.1177/0003319716639187
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid is a Useful Tool to Predict Contrast-Induced Nephropathy

Abstract: Developing contrast-induced nephropathy (CIN) after primary percutaneous coronary intervention (pPCI) has a negative impact on survival and morbidity. We assessed the predictive value of serum uric acid (SUA) for the development of CIN in patients with ST-segment elevation myocardial infarction (STEMI) who underwent pPCI. Contrast-induced nephropathy was defined an increase of ≥25% or ≥0.5 mg/dL in creatinine concentrations within 72 hours after pPCI. Patients were divided into 2 groups according to admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…The risk of AKI was 16% higher with each 1 mg increase in SUA [128]. SUA level is a significant predictor of contrast-induced nephropathy (CIN) [129], [130]. UA lowering with allopurinol in addition to saline hydration was associated with significantly lower incidence of CIN compared to saline hydration alone or saline hydration plus N-acetyl cysteine [130].…”
Section: Uric Acid and The Kidneymentioning
confidence: 99%
“…The risk of AKI was 16% higher with each 1 mg increase in SUA [128]. SUA level is a significant predictor of contrast-induced nephropathy (CIN) [129], [130]. UA lowering with allopurinol in addition to saline hydration was associated with significantly lower incidence of CIN compared to saline hydration alone or saline hydration plus N-acetyl cysteine [130].…”
Section: Uric Acid and The Kidneymentioning
confidence: 99%
“…Interestingly, radiocontrast causes an acute uricosuria [41], [46] that may potentially play a role in injury. Indeed, an elevation in serum uric acid, even at modest levels, is known to increase the risk for contrast-induced AKI [47], [48]. A recent meta-analysis by Kanbay et al that included 10 studies reported that elevated levels of serum uric acid were associated with a twofold increased risk for the development of radiocontrast-induced AKI (pooled odds ratio 2.03; 95%CI 1.48–2.78) [49].…”
Section: Uric Acid In Acute Kidney Injurymentioning
confidence: 99%
“…11 Recently, uric acid has been a key area of focus as a potential causal factor in a multitude of diseases including but not limited to hypertension, nephropathy, atherosclerosis, heart failure and acute kidney injury. [12][13][14][15][16][17][18] The common pathophysiologic denominator of these pathways is thought to be oxidative stress and inflammation resulting from a hyperuricemic state. 19 In vitro studies demonstrated that the pro-oxidative and pro-inflammatory state induced by hyperuricemia leads to microvascular dysfunction through stimulation of vascular smooth muscle cell proliferation, inhibition of endothelial cell function and activation of renin-angiotensin system.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%